Unistellar eVscopes: Smart, portable, and easy-to-use telescopes for exploration, interactive learning, and citizen astronomy. (January 2020) - Marchis, Franck; Malvache, Arnaud; Marfisi, Laurent; Borot, Antonin; Arbouch, Emmanuel
Abstract: Unistellar has created the Enhanced Vision Telescope (eVscope), a compact telescope that amplifies light so users can see hundreds of nebulae and galaxies directly through its electronics eyepiece. It can also pinpoint and identify objects in the sky, making amateur astronomy fun and more accessible to the public. Thanks to its sensitivity and accuracy, the eVscope is a powerful tool able to generate data that can be used by scientists to search for transient events like supernovae, near-Earth asteroids, and comets. This constellation of small, & smart telescopes could also enhance and supplement data generated by the small number of large telescopes operating today. Unistellar initiated a partnership with the SETI Institute to identify and implement scientific applications for a network of eVscopes. We summarize in this article the technology behind the eVscope and its real-time data processing (Enhanced Vision, Automatic Field Detection), then show several applications accessible to future users, including asteroid occultations, the detection of the atmosphere of Pluto and observations of near-Earth asteroids. The Unistellar network has the potential to make citizen astronomy a popular reality by offering all users (new or experienced) a tool to explore the night sky with a powerful and reliable instrument while they contribute to scientific investigations. Highlights: The Enhanced Vision Telescope (eVscope) of Unistellar is a digital telescope. The eVscope has a unique design, its smart and easy to use so made for the public. Thanks to a partnership with SETI Institute users can become citizen astronomers. We tested the eVscope potential for the study of asteroids. We conducted asteroid occultation campaigns, and detected Pluto's atmosphere.